Assessment of serum testosterone in females with acne vulgaris in Erbil city - Ahmed, Yousif Bahaaddin; Fattah, Fatin Qaraney (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Acne vulgaris is a chronic inflammatory disease of the pilosebaceous units, characterized by comedones, papules, pustules and nodules. Acne affects primarily the face, neck, upper trunk. Acne typically begins at puberty and it is often the first sign of increased sex hormone production. In all women with acne the possibility of hyperandrogenic state should be considered. The aim of this study was to determine the relationship between abnormal testosterone level and other virilising signs in young females with acne vulgaris. Methods: This case-control study was carried out from April 2013 to January 2014 in the consultation Department of Dermatology and Venereology at Rizgary Teaching Hospital in Erbil city. Sixty females were considered group A (case group with acne) and 60 females were considered as group B ( control group) without acne. Results: The mean±SD serum testosterone level was significantly higher among patients with acne compared to the control group (0.51 ng/ml ± 0.27 compared to 0.31 ng/ml ± 0.12, P ˂0.05). Irregular cycle was found in 28 cases (46.6%). Conclusion: The study showed presence of a significant association between serum testosterone level and acne vulgaris in female patients.